Design Empathy in Students’ Participatory Design Processes - Bosch, Noora; Härkki, Tellervo; Seitamaa-Hakkarainen, Pirita (Design and Technology Education: An International Journal, 2022)
In this exploratory case study, we focus on empathy, an important aspect of contemporary design practices. We aim to explore how design empathy manifested in students’ design processes. A three-month participatory design project was created and assigned to students (aged 14–15), with the following brief: ‘co-design and make an e-textile product for kindergarteners according to their wishes and needs’. We examined 72 end-user-related design episodes from two student teams (six students in total), analysing students’ end-user-related considerations, as well as different signs and dimensions of empathy. Our findings indicate that the students considered, discussed and referred to topics concerning end users during the process. Signs and dimensions of empathy were found in the various end-user-related discussions and empathetic considerations, through which end-user-friendly design products materialised. We conclude that students could practise empathic design by acknowledging end users in multiple concrete and abstract ways and designing and manufacturing meaningful products for end users. This offers new opportunities for engaging students in reflective (digital) design and making, targeting design-literate citizens in the 21st century. However, this novel field requires further studies in educational contexts other than higher education, which currently has the best research coverage.